Helping older people: is there an app for that? - Cunha, António (2016)
From social networks to health and fitness, everyday a lot of mobile devices applications (apps) are being developed. The variety and availability is such that people start to think that indeed “there's an app for everything”. Many of these apps address either problems or characteristics that affect older people and that are related with the ageing process (e.g. memory and visual aids apps). They can effectively help people and are under constant evolution. However, the lack of knowledge about these available technological aids can undermine its dissemination and consequently the help that people really receive, especially those who need it the most: older people. As such, a methodological search for available aid apps was made both in Google Play and in iTunes: 536 were selected, their classification analysed and the kind of help that they provide identified. It was noted that either in Google Play or in iTunes the apps’ categories are similar. Furthermore, it is not easily perceived what the type of help that each app can provide is and how is it provided. Hence, based on the results from the aforementioned methodological search, this paper proposes a new scalable tree-based classification methodology for aid apps, which is considered more suited to perceive what the available aid apps for mobile devices are. The existing apps were then characterized based on the proposed classification, to determine what the main aid that they provide is.